FEASIBILITY STUDY BY MEANS OF CAPTURE FISHING IN UPT PURSE SEINE PORT AND MANAGEMENT OF MARINE AND FISHERY RESOURCES (P2SKP) TAMBAK Rejo, BLITAR, EAST JAVA - Onky Cucuk; Ganjar Adhywirawan; Sri Samsundari (IJOTA (Indonesian Journal of Tropical Aquatic), 2023)
This research was conducted for 30 days, ie from 15 January to 17 February 2018 at UPT Port and Management of Marine and Fishery Resources (P2SKP) Tambakrejo, Wonotirto District, Blitar Regency, East Java Province. The purpose of this research is to know the process of purse seine work and business feasibility by using purse seine fishing equipment in Tambakrejo Village and to know the efficiency of purse seine fishing equipment to the people's income in Tambakrejo village.The method used in this research is descriptive method with survey technique. As for the object of his own research is the owner of the ship purse seine in Tambakrejo Village. Methods of data collection using several techniques of observation techniques, interview techniques, and literature study techniques. The collected data was then analyzed to determine the feasibility of purse seine fishing effort in Tambakrejo village.The result of this research shows that purse seine fishing business is very feasible to run as seen from NPV value of 15348.15, Net B / C Ratio of 2.00, IRR of 242.10%, BEP production of 178.62 Kg, BEP price of 2,399,999,51 and Payback Period of 0.44, from the value can be concluded that fishing effort by using purse seine fishing equipment in Tambakrejo Village is very feasible to run.Therefore research is done to provide a source of information to fishermen and boat owners that fishing effort by using purse siene fishing equipment is feasible to run because it will increase the economic value of fishermen communities.